PENDIDIKAN MODERASI BERAGAMA DI SMA NEGERI 5 DEPOK PERSPEKTIF SOSIAL-KONSTRUKTIVISME - Renny Ariany; Akhmad Sodiq; Dimyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explain the implementation of religious moderation education at SMA Negeri 5 Depok through the lens of socio-constructivism. It focuses on school policies related to religious moderation and the strategies employed by religious education teachers in transmitting these values to students. Using a qualitative descriptive approach based on Lev Vygotsky’s socio-constructivist theory, data were collected through interviews with the principal, vice principal for curriculum affairs, religious education teachers, and students, as well as documentation including questionnaires, the school’s official website, curriculum documents, textbooks, and relevant articles. The findings reveals that SMA Negeri 5 Depok integrates the principles of religious moderation into its vision, mission, and school activities within its diverse religious environment. Teachers apply constructive and reflective learning strategies that encourage critical thinking and connecting religious values with social contexts. The learning process incorporates discussions, presentations, and case studies on intolerance, radicalism, and interreligious conflict. Positive social interactions between teachers and students support the growth of tolerance and religious harmony. In conclusion, religious moderation at SMA Negeri 5 Depok is practiced not only in formal lessons but also across school culture, fostering inclusivity and respect for religious diversity.